RISK FACTORS FOR PREMATURE BIRTH IN INDONESIA - Hafiza Ajeng Dianing Sukma; Sagar Tiwari (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2021)
Indonesia is currently taking on the challenge of the relatively high number of neonatal deaths influencing maternal and child health. Premature birth is the most significant contributor to the number of neonatal deaths. The occurrence of premature birth is motivated by various risk factors. Knowing the magnitude of the relationship between several risks, namely maternal age, location, parity, and maternal smoking habits with preterm birth incidents was the aim of this study. The 2017 Indonesian Demographic and Health Survey (IDHS) was a source of data used. This study employed a cross-sectional approach and then processed the results with univariate and bivariate tests. The results showed a relationship between maternal age and residential area with the premature birth, where mothers under 20 years and over 35 years had a higher probability of giving birth prematurely. The area of residence, which was divided into rural and urban, also had a relationship with premature birth. The parity and smoking habits showed no association with preterm birth. Education, Antenatal Care (ANC), and other various efforts to emphasize maternal and child health care during pregnancy need to be continuously improved to reduce preterm birth rates in Indonesia.